2021
DOI: 10.1111/gwat.13108
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Nitrate Removal in Anoxic Groundwater during River Flooding of Riparian Zones

Abstract: A numerical study demonstrates the effects of flooding on subsurface hydrological flowpaths and nitrate removal in anoxic groundwater in riparian zones with a top peat layer. A series of two-dimensional numerical simulations with changing conditions for flow (steady state or transient with flooding), hydrogeology, denitrification, and duration of flooding demonstrate how flowpaths, residence times, and nitrate removal are affected. In periods with no flooding groundwater flows horizontally and discharges to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The interaction and change of the temperature field must be considered in the development of the control system [32,33]. Only with a detailed calculation of the intensity of mutual influence and considering the results obtained when determining the permissible production volumes, the stability of the operation process and the structural integrity of the fields can be guaranteed [34,35].…”
Section: Control System Synthesis Resultsmentioning
confidence: 99%
“…The interaction and change of the temperature field must be considered in the development of the control system [32,33]. Only with a detailed calculation of the intensity of mutual influence and considering the results obtained when determining the permissible production volumes, the stability of the operation process and the structural integrity of the fields can be guaranteed [34,35].…”
Section: Control System Synthesis Resultsmentioning
confidence: 99%
“…The study of nutrient transport continues to be one of the major reasons for investigating groundwater–surface water interactions, not just to assess the contaminant load to a surface water body, that is, a lake, by combining conservative and nonconservative tracers (Kristensen et al, 2018), but also to quantify the effects of redox conditions in groundwater on the fate of nitrate before discharging to streams (Jensen et al, 2021; Nilsson et al, 2017; Ribas et al, 2017). In the field of wetland restoration, problems due to the release of phosphate are a new concern (Audet et al, 2020).…”
Section: Historical Overview Of Studiesmentioning
confidence: 99%
“…This will affect the riparian flow path type. For example, Jensen et al (2017Jensen et al ( , 2021 have shown that flooding leads to groundwater upwelling near the flood limit and groundwater-fed surface flow to the stream. This can have positive and negative effects on nitrate removal, depending on whether there is a top organic peat layer.…”
Section: Climate Change and Groundwater-surface Water Interactionsmentioning
confidence: 99%
See 1 more Smart Citation